Активізація контролю знань з паралельного вивчення економіки та англійської мови - Яковенко, Р. В.; Yakovenko, R. (ЦНТУ, 2018)
Посібник містить зміст завдання трьох рівнів, що спрямовані на засвоєння економічних та лінгвістичних знань. The manual contains the content of the task of three levels, aimed at the acquisition of economic and linguistic knowledge.
Activation of knowledge control on parallel study of economics and English
Keywords: потреби; ресурси; ринок; попит; пропозиція; витрати; прибуток; needs; resources; market; demand; supply; costs; profit